Motivational Factors Influencing Retention of Village Health Workers in Rural Communities of Bhutan. (July 2019) - Tshering, Dolley; Tejativaddhana, Phudit; Siripornpibul, Taweesak; Cruickshank, Mary; Briggs, David
Village health workers (VHWs) are the first contact extending vital health services to unreached and underserved communities in Bhutan. VHWs truly embody the principles of primary health care and are effective catalysts in promoting community health. This study identifies and confirms factors motivating VHWs to remain in the health care system. This is a quantitative study with a cross-sectional survey design. Two-stage cluster sampling was used with VHWs from 12 districts representing 3 regions of Bhutan. Data were collected using pretested semistructured questionnaires. Confirmatory factor analysis was used for data analysis. Findings reveal a 4-factor model of motivations among VHWs that includes social, personal, job related, and organizational factors. Among these, the social factor most significantly motivates VHWs to remain in the health care system. VHW motivation can be further fostered by providing a holistic combination of financial and nonfinancial incentives that recognize intrinsic needs and empower innate altruism.